INTEGRASI KOMPETENSI KEBAHAGIAAN DALAM PENGEMBANGAN SIKAP SPIRITUAL DAN SOSIAL SISWA - Khairunnisa, Muthia Fadhila; Salsabilla, Tiara; Apsari, Nurliana Cipta (Social Welfare Study Program, 2023)
Abstract. Education curriculum is one of the most important aspects in the learning process. In Indonesia’s 2013 Curriculum (K13), spiritual and social traits become one of the three graduation competencies for students. However, character development and planting a sense of joy in learning for students have not become the main focus in Indonesian education. The government of Delhi, India, developed an innovation called Happiness Curriculum, where it includes three Happiness Competencies, which are: mindfulness, critical thinking and reflection, and social-emotional skills. This study is important because developing the character of critical, mindfulness and able to self-reflection will assist the Indonesian young generation to be more prepared to address challenges and issues of the future. This research aims to identify the urgency and how can the Happiness Competencies be integrated into the curriculum in Indonesia to increase the spiritual and social traits competency for students at school. The method used is literature review. The result shows that the Happiness Competencies based on the Happiness Curriculum from Delhi, India, can be integrated starting from the teacher and the surrounding environment that supports the said transformation, considering that mental health at school is one of the issues that should become the concern of actors in the education sector. Keyword: Education, curriculum, happiness competency, spiritual traits, social traits. Abstrak. Kurikulum pendidikan merupakan salah satu aspek penting dalam proses pembelajaran. Dalam Kurikulum 2013 (K13) di Indonesia, sikap spiritual dan sosial menjadi salah satu dari tiga standar kompetensi kelulusan siswa. Namun, pengembangan karakter dan penanaman rasa senang belajar kepada siswa belum menjadi fokus utama dalam pendidikan Indonesia. Pemerintah Delhi, India, mengembangkan inovasi bertajuk Happiness Curriculum yang mencakup tiga Kompetensi Kebahagiaan, yakni: mindfulness, critical thinking, and reflection, serta social-emotional skills. Penelitian ini bertujuan untuk mengidentifikasi urgensi serta bagaimana Kompetensi Kebahagiaan tersebut dapat diintegrasikan kedalam kurikulum di Indonesia guna meningkatkan kompetensi sikap spiritual dan sosial siswa di sekolah. Penelitian ini penting karena pengembangan karakter siswa yang kritis, mampu merefleksikan diri dan memiliki kemampuan mindfulness dapat membantu generasi muda Indonesia menjadi generasi yang lebih siap menatap tantangan di masa depan. Metode yang digunakan ialah studi kepustakaan. Hasil penelitian menunjukkan kompetensi kebahagiaan berdasarkan Happiness Curriculum dari Delhi, India, dapat diintegrasikan dimulai dengan guru dan lingkungan sekitar yang mendukung perubahan tersebut, menimbang bagaimana kesehatan mental di lingkungan sekolah juga menjadi salah satu isu yang menjadi perhatian pelaku pendidikan termasuk pekerja sosial di sekolah. Kata kunci: Pendidikan, kurikulum, kompetensi kebahagiaan, sikap spiritual, sikap sosial.